(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
Herbal drugs are widely used to treat and prevent various diseases with more than 80% of people worldwide relying on them for their primary healthcare. Polyherbal formulations express high effectiveness in various diseases due to their synergistic effect. Herbal formulations are required to standardize in order to assess their quality, purity, and biological efficacy. The present study aimed to prepare a polyherbal formulation comprising of lyophilized ethanolic extracts of three well known anti-diabetic herbal drugs (Momordica charantia, Andrographis paniculata and Withania somnifera), and three formulations were developed in combination ratios (1:1:1, 2:1:2, and 2:2:1) respectively and to develop high-performance liquid chromatography (HPLC) method for assessment of purity, standardization and estimation of markers. In addition, developed formulations were optimized on the basis of oral glucose tolerance test (OGTT). Standardization of developed polyherbal formulations was performed by using respective biological markers (Vicine, andrographolide, withaferin-A and withanolide-A) by HPLC technique. HPLC was performed using RP-18, Merck column to study the presence and quantification of respective markers at a wavelength of 237 nm. The HPLC study revealed the presence of vicine, andrographolide, withaferin-A, and withanolide-A in quantifiable amounts in respective extracts. OGTT study was performed using normal albino Wistar rats at a drug dose of 500 mg/kg body weight. Rats were divided into six groups, including three combination ratios and standard (Metformin) group. An optimized ratio 2:2:1 showed a significant decrease in blood glucose levels compared with standard control rats.